SAE Technical Paper Series 1977
DOI: 10.4271/770407
|View full text |Cite
|
Sign up to set email alerts
|

Convective and Radiative Heat Transfer in a High Swirl Direct Injection Diesel Engine

Abstract: Thermal radiation laws and the concept of black body 2.2.3 Attenuation laws and gas emissivity 2.2.4 Thermal radiation in diesel engines 2.2.4(a) Radiation from non-luminous gases 2.2.4(b) Radiation from clouds of luminous particles 2.2.5 Prediction of radiant heat transfer from flames using Hottel's approach 2.2.5(a) Mean beam length and eJ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…A higher engine speeds leads to a higher in-cylinder gas flow and hence a higher convection coefficient. This is confirmed by [21,20,22]. The peak values are predicted by both simulations since their relative error is smaller than the measurement error on the peak convection coefficient.…”
Section: Effect Of Engine Settingssupporting
confidence: 62%
“…A higher engine speeds leads to a higher in-cylinder gas flow and hence a higher convection coefficient. This is confirmed by [21,20,22]. The peak values are predicted by both simulations since their relative error is smaller than the measurement error on the peak convection coefficient.…”
Section: Effect Of Engine Settingssupporting
confidence: 62%
“…Dent and Sulaiman [7] investigated the applicability of using a forced convective turbulent heat transfer correlation for flow over a flat plate to predict the convective heat flux in a high swirl direct injection diesel engine. In this investigation, the heat transfer correlation was based on the Nusselt number as derived by Kreith [8].…”
Section: Methodsmentioning
confidence: 99%
“…Other correlations for the heat transfer coefficient have been used in the past for direct injection diesel engines, such as Annand [9], Woschni [10], and Le Feuvre et al [11]. The correlation used by Annand [9] is very similar to Dent and Sulaiman [7]. An important difference is Dent and Sulaiman [7] used the swirl velocity as the characteristic velocity and the bore circumference as the characteristic length in the Reynold's number.…”
Section: Methodsmentioning
confidence: 99%
“…Hassan [21] (with a coaxial 165 thermocouple) and Dao et al [23] demonstrated that the peak values of the heat flux increased. Dent and Suliaman [22] (with a thin film sensor) showed that the heat flux was only significantly higher around TDC within an interval of 90…”
Section: Influence Of Engine Speedmentioning
confidence: 99%